Being and doing in organizations: agents, actors or persons - Llewellyn, Sue (Proceedings of Pragmatic Constructivism, 2011)
It is the aim of this article to understand what it means to be an agent , actor or person in an organization using theoretical arguments from Giddens and Archer.